De las cifras a la realidad.Las industrias culturales y creativas en Latinoamérica: un escenario en construcción - Higidio Henao, Leydi (Editorial Uniagustiniana, 2018)
This chapter presents advances found in the study of different organizations and the results of pilot projects of creative and cultural industries (cci) in Latin Ameri-ca. It also establishes some parameters for cci develop-ment in theoretical and academic terms including the observed in practice. In Latin America, programs and projects have been carried out and, although they have shown a new panorama, concepts and policies are still being analyzed and built. Analysis made by organiza-tions such as the Organization of Ibero-American States (oei), the United Nations Educational, Scientific and Cul-tural Organization (unesco), the International Confeder-ation of Societies of Authors and Composers (cisac) and Ernst & Young (ey) (2015), among others, have focused their studies on the most important variables for the development of these new industries. However, there is still a gap regarding the real scope and impact of what is called a motor of socio-economic development for the territory. This chapter presents two relevant cases in the region: i) the Cultural Industries Project of Cali, and ii) the Trama Project of Chile. These are pilot projects that allow us to observe some results in two commu-nities located in different places in regards to creative and cultural entrepreneurship promotion, organization of sectors, networks shaping, and the impact of these processes in a production and social framework; and in-vites to a deep study of these cases for the evolution of the cci in the region.